Electron-positron pair creation under Gaussian and super-Gaussian pulse trains - X. X. Zhou; X. N. Cao; C. K. Li; N. S. Lin; Y. J. Li (European Physical Journal C: Particles and Fields)
Abstract The electron-positron pair (EPP) creation under Gaussian and super-Gaussian pulse trains are studied by the computational quantum field theory (CQFT) in the single-photon regime. The details of the EPP creation are studied from the time evolution of the EPP number, energy spectra and spatial distribution of the electrons. The results indicate that the final created EPPs is the non-linear accumulation of the multi-pulses, which depends on the time interval, pulse shape and pulse number. The optimal time interval can be chosen based on the pulse resonance condition, which is derived by the perturbation method. Besides, steeper super-Gaussian pulses and adding more pulses facilitate the EPP creation as well. The results indicate that, under optimal multi-pulse parameters, the number of the EPPs obtained is much larger than the sum of the EPPs created under the same number of single pulses. This finding not only can enhance the EPP creation, but also can improve the multi-pulse utilization and guide future experimental research on the EPP creation.